2009
DOI: 10.1016/j.pain.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinal role of protein kinase C in oxaliplatin-induced neuropathy in rat

Abstract: a b s t r a c tOxaliplatin is a platinum-based chemotherapy drug characterized by the development of a painful peripheral neuropathy which is reproduced in rodent animal models with features observed in humans. Our focus was to explore the alterations of intracellular second messengers at supraspinal level in oxaliplatin-induced mechanical hyperalgesia. In our experiments, chronic administration of oxaliplatin to rats induced mechanical hyperalgesia which lasted for many days. When the hyperalgesic rats were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…Our group has demonstrated an oxaliplatin-dependent alteration at the spinal and supraspinal levels in the rat of PKCγ [10] . Here, we confirmed the previous data in oxaliplatin-treated mice supporting a correlation between enhanced mechanical nociception with increased phosphorylation of PKCγ in PAG and thalamus brain regions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our group has demonstrated an oxaliplatin-dependent alteration at the spinal and supraspinal levels in the rat of PKCγ [10] . Here, we confirmed the previous data in oxaliplatin-treated mice supporting a correlation between enhanced mechanical nociception with increased phosphorylation of PKCγ in PAG and thalamus brain regions.…”
Section: Discussionmentioning
confidence: 91%
“…Given the known molecular interactions between the GAP43 mRNA, cytoskeleton apparatus and ELAV proteins, we sought to investigate the role of the HuD protein in oxaliplatin-induced neuropathy and the possible HuD-mediated modulation of these regulatory and structural proteins in this study. Increased phosphorylation of protein kinase C (PKC) γ isoform within the thalamus and periaqueductal grey (PAG) was observed after oxaliplatin chronic treatment, and the hyperalgesic effect was reversed in the presence of selective PKC inhibitor calphostin C, supraspinally administered [10] . In order to relate changes at the molecular and cellular levels to the development of sensory alterations, we also examined a relationship between the PKC pathway and GAP43, known as indicator of injury-induced molecular changes that could be related to the alterations in sensory function.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin-induced neuropathy was shown to be involved in the activation of PKC within the thalamus and periaqueductal area in the brain. 10 In addition, increases in ERK1/2 phosphorylation and c-Fos expression in the spinal cord have been associated with chronic pain. 17,18 Previous studies have established that activation of PKC in the spinal cord dorsal horn plays a critical role in the transmission of nociceptive signals following mustard oil (TRPA1 activator) application.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Oxaliplatin induces mechanical allodynia by inducing an upregulation of specific g isoforms of PKC and increasing phosphorylation of the g/E PKC isoforms within the thalamus and periaqueductal area in the brain. 10 In addition, oxaliplatin induces apoptosis by activating extracellular signal-regulated kinases 1/2 (ERK1/2) in rat dorsal root ganglia cells. 11 These findings suggested that neuropathy associated with oxaliplatin may be mediated by PKC and ERK1/2 activation in the brain or spinal cord.…”
mentioning
confidence: 99%
“…In the previous study, repeated administration of oxaliplatin caused cold hyperalgesia in the early phase and mechanical allodynia in the late phase (2 weeks after first administration). [25][26][27] Conversely, cold hyperalgesia/allodynia was not observed in the NC-4016-treated rats. Oxalate is well known as a chelator of both Ca2 were shown to decrease oxaliplatin-induced neuropathy without affecting anticancer efficacy.…”
Section: Discussionmentioning
confidence: 99%